2021
DOI: 10.3390/genes12111829
|View full text |Cite
|
Sign up to set email alerts
|

CircNFIC Balances Inflammation and Apoptosis by Sponging miR-30e-3p and Regulating DENND1B Expression

Abstract: Disordered inflammation and apoptosis are closely related to diseases, and inflammation can also promote cell apoptosis, where growing evidence has shown that circular RNAs (circRNAs) play important roles. Lipopolysaccharide (LPS) is the main component of the cytoderm of gram-negative bacterium, which can cause inflammatory responses in macrophages. We constructed an inflammatory model by exposing chicken macrophage cell lines (also known as HD11) to LPS for in vitro experiments. In this study, we validated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 68 publications
(83 reference statements)
1
3
0
Order By: Relevance
“…Both RNA and protein levels of IL-1β decreased following miR-30e-3p transfection, and direct interaction of miR-30e-3p -IL-1β was identified by 3'UTR luciferase assay. Similar to our findings, Chen et al showed that miR-30e-3p is a part of inflammation and apoptosis regulator complex with CircNFIC and DENND1B and regulates IL-1β secretion in chicken macrophage cell lines [27]. Also, the role of miR-30e-3p on drug resistance was reported in different cancer types [28,29].…”
Section: Discussionsupporting
confidence: 90%
“…Both RNA and protein levels of IL-1β decreased following miR-30e-3p transfection, and direct interaction of miR-30e-3p -IL-1β was identified by 3'UTR luciferase assay. Similar to our findings, Chen et al showed that miR-30e-3p is a part of inflammation and apoptosis regulator complex with CircNFIC and DENND1B and regulates IL-1β secretion in chicken macrophage cell lines [27]. Also, the role of miR-30e-3p on drug resistance was reported in different cancer types [28,29].…”
Section: Discussionsupporting
confidence: 90%
“…In the nucleus, circRNAs combine with RNA polymerase II to regulate the transcriptional activity [ 26 ]. Alternatively, in the cytoplasm, circRNAs act as molecular sponges to bind with specific miRNA to promote the function of target genes [ 27 , 28 , 29 , 30 , 31 , 32 ]. For example, it has been demonstrated that circPTPN4 can stimulate NAMPT expression by sponging miR-499-3P in the cytoplasm and acting as a competing endogenous RNA [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its downregulation should indicate higher expression levels of the target gene CAMK2A, which, in turn, would activate the mentioned functions. Other dysregulated miRNAs in common such as miR-126-5p, miR-30e-3p and miR-186-5p have been related with the inflammatory signal [21][22][23] , pointing towards an active response to the vaccines and the adjuvant in spleen. There were few miRNAs differentially expressed after aluminium adjuvant-only treatment, and only four were exclusive to that treatment, even if we did not find any DE miRNA between both treatment groups.…”
Section: Discussionmentioning
confidence: 99%